2018
DOI: 10.1021/acs.jctc.8b00311
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of TD-DFT Geometries: A Fresh Look

Abstract: We benchmark a panel of 48 DFT exchange-correlation functionals in the framework of TD-DFT optimizations of the geometry of valence singlet excited states. To this end, we use a set of 41 small- and medium-sized organic molecules for which reference geometries were obtained at high level of theory, typically, CC3 or CCSDR(3), with the aug-cc-pVTZ atomic basis set. For the ground-state parameters, the tested functionals provide average deviations that are small (0.010 Å and 0.5° for bond lengths and valence ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
126
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(136 citation statements)
references
References 153 publications
10
126
0
Order By: Relevance
“…The PBE0 functional was chosen based on benchmark papers for heterocyclic rings. [39][40] Stationary points with no imaginary frequencies were confirmed through frequency calculations. The stability of the wave function and spin contamination for the triplet state were checked.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…The PBE0 functional was chosen based on benchmark papers for heterocyclic rings. [39][40] Stationary points with no imaginary frequencies were confirmed through frequency calculations. The stability of the wave function and spin contamination for the triplet state were checked.…”
Section: Methodsmentioning
confidence: 84%
“…Time‐dependent DFT (TD‐DFT) was used for the S 1 state optimizations while the unrestricted version of DFT was used for T 1 state optimizations. The PBE0 functional was chosen based on benchmark papers for heterocyclic rings . Stationary points with no imaginary frequencies were confirmed through frequency calculations.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Brémond et al [ 65 ] reported the first extensive assessment of the accuracy of TD‐DFT for geometries of small organic molecules in valence excited states. Testing a panel of 48 different functionals and using geometries previously calculated [ 66 ] with CASPT2 or a high‐order coupled cluster (CC) method (CC3 [ 67 ] or CCSDR(3) [ 68 ] ) as reference, these authors concluded that excited‐state bonds lengths obtained with TD‐DFT are on average of somewhat lesser quality than the corresponding DFT ground‐state bond lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we want to verify that the observed improvement on energy properties of weakly interacting molecules is not performed at the expense of a basic property such as molecular geometry but that the performance improvement on both properties stays in close correlation. [21,37] Our benchmarking investigation focuses on the CCse and B3se databases of accurate structural parameters introduced some years ago by Barone and coworkers. [38][39][40][41] The former includes a collection of 21 small organic molecules whose reference covalent structural parameters are derived from a mixed coupled-cluster singles and doubles plus perturbative triples [CCSD(T)] and experimental protocol.…”
Section: Introductionmentioning
confidence: 99%